Pengaruh Disiplin Kerja terhadap Prestasi Kerja Pegawai pada Kantor Dinas Sosial Kota Bima - Novita, Sri Devi; Mukhlis, Mukhlis; Kusumayadi, Firmansyah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to determine the effect of work discipline on employee work performance. The sample in this research was 33 ASNs using a purposive sampling technique. Data collection techniques using observation, questionnaires and literature study. The data analysis technique uses simple linear regression assisted by SPSS for widows. The research results show that work discipline has a significant effect on the work performance of Bima City Social Service employees.